A New Hyaluronan Modified with β-Cyclodextrin on Hydroxymethyl Groups Forms a Dynamic Supramolecular Network - Kovačević, Jelica; Prucková, Zdeňka; Pospíšil, Tomáš; Kašpárková, Věra; Rouchal, Michal; Vícha, Robert (Molecules (Basel, Switzerland), 2019)
A new hyaluronan derivative modified with β-cyclodextrin units (CD-HA) was prepared via the click reaction between propargylated hyaluronan and monoazido-cyclodextrin (CD) to achieve a degree of substitution of 4%. The modified hyaluronan was characterized by 1H-nuclear magnetic resonance spectroscopy (NMR) and size exclusion chromatography. Subsequent 1H-NMR and isothermal calorimetric titration experiments revealed that the CD units on CD-HA can form virtual 1:1, 1:2, and 1:3 complexes with one-, two-, and three-site adamantane-based guests, respectively. These results imply that the CD-HA chains used the multitopic guests to form a supramolecular cross-linked network. The free CD-HA polymer was readily restored by the addition of a competing macrocycle, which entrapped the cross-linking guests. Thus, we demonstrated that the new CD-HA polymer is a promising component for the construction of chemical stimuli-responsive supramolecular architectures.
Keywords: host-guest systems; click chemie; Hyaluronic Acid; Click Chemistry; supramolecular network; beta-Cyclodextrins; molekulární struktura; Molecular Structure; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; click reaction; Polymers; kalorimetrie; Calorimetry; polymery; beta-cyklodextriny; sodium hyaluronan; cyclodextrin; kyselina hyaluronová